Inclusion Relation between Various Subclasses of Harmonic Univalent Functions Associated with Wright's Generalized Hypergeometric Functions. (28th November 2020) - Themangani, Rajavadivelu; Porwal, Saurabh; Magesh, Nanjundan
Abstract : The purpose of the present paper is to obtain some inclusion relation between various subclasses of harmonic univalent functions by applying certain convolution operators associated with Wright's generalized hypergeometric functions.